Effects of storage on volatile organic components and physiological properties of different storage-tolerant rice varieties - Dawei Zhu; Xin Zheng; Huiyin Dong; Xingquan Liu; Xianqiao Hu; Mingxue Chen; Xin Liu; Yafang Shao (Food Chemistry: X)
The effects of storage on rice flavor among different rice varieties have not been well studied. To address this gap, we analyzed volatile organic components (VOCs) identified by gas chromatography-ion mobility spectrometry (GC-IMS) and related physicochemical properties of different storage-tolerant rice varieties during storage. The results showed that VOCs of four rice varieties significantly changed after 6 months of storage; OPLS-DA analysis classified the four rice varieties into two groups. There were fewer (N81 and JH1) and more significant changes (N84 and ZJ96) after storage, and the hexanal and 2-pentylfuran were considered the key VOCs for flavor changes during storage. Lipoxygenase (LOX) activity first increased and then decreased, while antioxidant activities decreased during storage. Under these conditions, oleic and linoleic acids were hydrolyzed. These results provide a better understanding of rice flavor changes after storage between different storable rice varieties.